Impact of age on short-term outcomes of liver surgery: Lessons learned in 10-years' experience in a tertiary referral hepato-pancreato-biliary center. Issue 20 (May 2017) - Ruzzenente, Andrea; Conci, Simone; Ciangherotti, Andrea; Campagnaro, Tommaso; Valdegamberi, Alessandro; Bertuzzo, Francesca; Bagante, Fabio; Mantovani, Guido; De Angelis, Michela; Dorna, Adriano E.; Piccino, Marco; Pedrazzani, Corrado; et al.
Abstract : Abstract: We investigate the surgical outcomes of patients undergoing hepatectomy according to different age intervals, identify the clinical factors related to surgical outcomes, and propose clinical risk scores for severe morbidity and mortality based on the clinical factors. Eight hundred three patients undergoing liver resection were divided into 3 groups: young patients (YP), <65 years (n = 387), elderly patients (EP), from 65 to 74 years (n = 279); very-elderly patients (VEP), ≥75 years (n = 137). Severe morbidity was 10.6%, 12.2%, and 17.5% ( P  = .103), and mortality was 0.3%, 1.4%, and 4.4% ( P  = .002) in group YP, EP, and VEP, respectively. Ischemic heart disease, cirrhosis, major hepatectomy, biliary tract-associated procedure, and red blood cells (RBC) transfusion ≥3 U were related with severe morbidity. Ischemic heart disease, cirrhosis, major hepatectomy, and RBC transfusion were independent risk factors for postoperative mortality. Age did not result an independent factor related to mortality and severe morbidity. Two different scores were developed and have proved to be statistically related with severe morbidity and mortality. Moreover, in patients with score ≥2, severe morbidity increased from 24.2% in YP, to 29.3% in EP, and to 40.0% in VEP, P  = .047. Likewise, mortality increased from 2.3% in YP, to 7.0% in EP, and to 22.7% in VEP, in patients with score ≥2, P  = .017. Age alone should not be considered a contraindication for hepatectomy. We identified factors and proposed 2 scores that can be useful to stratify the risk of morbidity and mortality after hepatectomy. Moreover, severe morbidity and mortality increases according to the different age intervals in patients with scores ≥2.